Clinical findings of tuberous sclerosis in Turkish children - Iscan, Akin; Kurul, Semra; Dirik, Eray (Journal of Pediatric Neurology, 2005)
We aimed to define clinical characteristics and laboratory findings of tuberous sclerosis in 17 patients. Age at presentation varied from 5 days to 13 years. Male to female ratio was 10/7. Genetic transmission was documented in 23.5% of cases. The most frequent presentation of the disease, hypomelanotic macules were seen in 94.1% (clinically visible in 15 subjects and visible with Wood’s light in 1 subject). Amongst skin manifestations facial angiofibromas were seen in 41.2%, forehead plaque in 5.9%, Shagreen patches in 23.5%. Brain involvement was documented in 94.1% of cases: subependymal nodules in 94.1%, cortical tubers in 76.5%. Seizures occured in 88.2% of the patients. The relative frequency of infantile spasms within all patients with symptomatic epilepsy was 26.7%. Cardiac rhabdomyoma was found in 37.5% of the patients, renal angiomyolipoma in 35.3%, retinal hamartoma in 33.3%, and hepatic angiomyolipoma in 33.3%. Up to one-half of all patients had normal intelligence and normal motor development. A large profile of neurological disability changing from a normal condition to a severe motor-mental retardation was noted in pediatric patients with tuberous sclerosis. Almost all of cases with motor-mental retardation had also epileptic seizures. The relative frequency of infantile spasms as compared with all kind of epilepsy was 26.7%. In addition to typical features of the disease several atypical manifestations such as autism, choreathetosis and hemangioma like cutaneous lesion were noted in this series.
Keywords: Tuberous sclerosis; children; choreathetosis; autism